Deformation geometry for materials scientists - Reid, C. N. (International series on materials science and technology ;, 1973)
Deformation Geometry for Materials Scientists presents the study of macroscopic geometry of deformation, particularly on crystalline solids. The book discusses a wide range of topics on the deformation of crystalline materials. The text discusses concepts on stress and strain on materials and tensile tests. Linear elastic and plastic deformations; and the macroscopic geometry mechanism of slip and deformation twinning are covered as well. Materials scientists, engineers, and students of materials science will find this book a great reference material.